Implementation of Bureaucratic Reform in Improving the Administrative Performance of Local Government: A Case Study of the Regional Secretariat of Sorong City - Yufa Yudhi Tehresia Imbiri; Karmanis Karmanis; Tri-Lestari-Hadiati (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the implementation of bureaucratic reform in improve the administrative performance of the Sorong City Regional Secretariat. The research uses a mixed-methods approach, combining quantitative and qualitative methods. Quantitative data were obtained by distributing questionnaires to 30 government apparatus respondents using the Likert scale and were analyzed using descriptive statistics and correlation analysis. Meanwhile, qualitative data were obtained through in-depth interviews with key informants and analyzed using thematic analysis and data triangulation. The results of the study show that the implementation of bureaucratic reform is positively related to the organization's administrative performance. The variables of policy communication, apparatus resources, and bureaucratic structure show a fairly strong correlation with administrative performance, with bureaucratic structure exhibiting the strongest relationship. Qualitative findings also show that bureaucratic reform has been carried out through simplifying procedures, updating SOPs, digitizing administration, and strengthening the performance reporting system. Theoretically, this research strengthens policy implementation theory and public organizational performance theory, which emphasize the importance of policy communication, human resource capacity, and the effectiveness of organizational structures in improving bureaucratic performance. However, this study has limitations in scope, as it is confined to a single organizational unit and a relatively small number of respondents. Therefore, further research is suggested to expand the research object in several regional apparatus organizations in order to obtain a more comprehensive picture of the implementation of bureaucratic reform at the local government level.